Sustaining innovation: How financial investment shapes patent creation in leading economies? - Gatari, Altis Puspa; Lubis, Firsty Ramadhona Amalia; Khoirudin, Rifki; Az Zakiyyah, Nurul Azizah; Kurniawan, Mahrus Lutfi Adi; Salim, Agus (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to analyze the role of liquidity in promoting patent-based innovation in the 10 countries with the highest innovation rates during the period 2012-2021. Using secondary data from the World Development Indicators (WDI), World Intellectual Property Organization (WIPO), and World Integrated Trade Solution (WITS), this study applies panel data regression method with Seemingly Unrelated Regression (SUR) approach to identify the influence of economic variables on the number of patents. The independent variables analyzed include equity x high technology, credit x high technology, industrial value added, exports, and liquidity. The results show that high-tech-based equity and credit have a significant influence on increasing the number of patents, while exports and liquidity do not show a meaningful influence. Value-added was also shown to have a significant contribution to innovation. These findings indicate that funding stability and long-term investment in research and development (R&D) determine innovation success more than the level of liquidity of the firm. Therefore, government policies and funding strategies should focus on improving access to high-tech-based financing as well as incentivizing R&D activities to foster a sustainable innovation ecosystem.